Current status and influencing factors of knowledge, attitude and practice of personal protection of healthcare workers in isolation wards of COVID-19 designated hospitals - Qian Liu; Yan Li; Chao Han; Qi Li (Frontiers in Public Health)
ObjectivesThe isolation treatment and special care of COVID-19 patients expose frontline healthcare workers (HCWs) involved in treatment to more risks of infection exposure. Therefore, investigating the current status of personal protection KAP of HCWs in isolation wards and its influencing factors will be helpful in improving personal protection in major public health events.MethodsResearch data came from COVID-19 designated medical institutions in Shandong Province from October to December 2022, and were collected through questionnaire surveys. The questionnaire is self-designed and composed of general information questionnaire, KAP questionnaire and anxiety and depression questionnaire. Univariate factor analysis and multiple linear regression analysis were used to study the influencing factors of KAP of the research subjects.ResultsIn terms of KAP Scores, the mean knowledge score was 6.82 ± 1.6, with 85.60% scoring at a medium level or below. The attitude mean score was 27.56 ± 4.1, and 78.60% held a favorable disposition toward personal protection measures. For practice, the mean score was 44.44 ± 5.6, with approximately 30.86% demonstrating room for improvement. Univariate analysis indicated significant differences in knowledge scores among HCWs with varying numbers of personal protective equipment (PPE) trainings and levels of depression and anxiety (p ≤ 0.05). Attitude scores differed significantly based on depression and anxiety levels (p ≤ 0.05). Practice scores varied significantly according to occupation, work experience, cumulative working time in isolation wards, and PPE training frequency (p ≤ 0.05). Multiple linear regression analysis revealed that increased PPE training frequency (β = 0.168, p = 0.007) and lower anxiety levels (β = −0.256, p ≤ 0.001) were associated with higher knowledge scores. Depression levels (β = −0.208, p = 0.001) were negatively associated with attitudes. Longer medical experience (β = 0.132, p = 0.029), more cumulative working time in isolation wards (β = 0.310, p ≤ 0.001), and lower anxiety levels (β = −0.129, p = 0.034) positively influenced practice scores.ConclusionIn summary, for HCWs in isolation wards, increasing the frequency of protective training and reducing anxiety will improve their personal protection knowledge; alleviating depression will cultivate a positive attitude toward personal protection; and relieving anxiety, along with longer job tenure and working hours, were associated with enhanced protective behaviors.